Analysis of Leadership and Work Discipline on the Performance of Non-ASN at the North Sumatra Cooperatives and SMEs Office - Kurniawan Syahputra; M. Chaerul Rizky; Abdi Setiawan (Riviera Publishing, 2026)
The performance of non-ASN employees is an important factor in supporting the achievement of government organizational goals. This study aims to analyze the influence of leadership and work discipline on the performance of non-ASN employees at the North Sumatra Cooperatives and SMEs Office. This study used a type of quantitative research with a descriptive and associative approach. The population in this study is all Non-ASN/Honorary employees and Assistants of the North Sumatra Cooperatives and SMEs Office which amounted to 70 employees, with saturated sampling techniques (census), so that the sample in this study amounted to 70 respondents. Primary data was collected through questionnaires arranged based on the Likert scale, while data analysis used multiple linear regression analysis techniques with the help of SPSS software. The results of the study showed that: leadership did not have a significant effect on the performance of non-ASN employees; work discipline has a positive and significant effect on the performance of non-ASN employees; leadership and work discipline simultaneously have a significant effect on the performance of non-ASN employees. The determination coefficient value (R²) of 0.367 showed that leadership and work discipline were able to explain 36.7% of the variation in the performance of non-ASN employees, while the remaining 63.3% were influenced by other variables outside of this study